PENGARUH QUALITY OF WORK LIFE TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI MEDIASI PADA PEGAWAI DINAS SOSIAL KABUPATEN KARANGASEM - Amelia Shanty, Ni Putu Deasy; Adnyani, I Gusti Ayu Dewi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.03.TAHUN.2023DO - 10.24843/EEB.2023.v12.i03.p18, 2023)
Employee performance is the result of achieving employee work by established regulations. The purpose of this study was to analyze the role of job satisfaction in mediating the effect of quality of work-life on employee performance. The theoretical basis used in this research is the theory of social exchange. The number of samples used is 63 employees, using a non-probability sampling method with a saturated sampling technique. Data was collected through interviews and questionnaires. The analytical technique used is descriptive statistical analysis, classical assumption test, path analysis, Sobel test, and VAF test. The results showed that the quality of work-life had a positive and significant effect on employee performance. Quality of work-life has a positive and significant effect on job satisfaction. Job satisfaction has a positive and significant effect on employee performance. Job satisfaction partially mediates the effect of quality of work-life on employee performance. The results of this study have implications for the development of human resource management science, especially for employees of the Karangasem Regency Social Service to pay more attention to the quality of work-life and employee job satisfaction, to improve employee performance .